PENGEMBANGAN KOLEKSI GUNA MEMENUHI KEBUTUHAN INFORMASI DI MTS EX PGA UNIVA MEDAN - Gusti aprila Pasaribu; Lutfia Malaya Alfa; Dhea Puspita; Duwi Juliani; Filza Alyani (CV. Arsy Persada Quality, 2024)
The developesent of collections in libraries is one of the important activities shot must be implemented by all types of libraries. With the developmear of the collection, the library is able to provide collections that fit the veeds of the library and the needs of the settlers so that their information needs will be fulfilled. The Library of sclwols as an educationel tool that supports teaching and learning activifes in the school, is required to always develop their collection in order to support the needs of information on students, reachers, and school managers. This article will explain briefly about the middle school libraries/Madrasch MTS then processes and nages that are performed in the development of the collection. The oapat is expected to orchestrame jucior high Scloud libraries/Madrasah MTS urulersted unul understowed the steps in the development of the collection to meet the needs of information in the school.